Dynamics of bank relationships in entrepreneurial finance - Takahashi, Hidenori (Journal of Corporate Finance, 2015)
This study examines the role of commercial bankers in banks' efforts to build relationships with small and young firms. Using Japanese IPO data, this study reveals that banks tend to provide an additional banker to firms with limited financial experts on the board. In addition, the banker's entry as a proxy to establish a lending relationship is more likely to occur before the bank's venture capital (VC) investment. These findings suggest that commercial banks provide bankers to supplement financial expertise in their client's firms and use this relationship to build subsequent VC investment.